PENGARUH PENGAWASAN PIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA PEGAWAI PERUSAHAAN DAERAH AIR MINUM ( PDAM ) KABUPATEN MALANG - Samiadji, Samiadji (Manajemen & Bisnis Jurnal, 2018)
Basically, companies need not only qualified, capable and skilled employees, but most importantly they are willing to work hard and are eager to achieve optimal work. One of the things that can optimize employees in work is with business progress, because with the business progress of employees can perform their duties to the maximum in accordance with the set targets. The purpose of this study is to analyze the influence of supervisory leadership, work motivation, and job satisfaction that contribute simultaneously and significantly to work business progress PDAM Malang Velage employees. In accordance with the principal problems and research objectives that have been formulated, then this type of research is quantitative research. The sample in this research is 157 employee PDAM Malang Velage. Data analysis method used is path analysis. Based on the data analysis found that : (1) the supervision of leadership and work motivation influence simultaneously and significantly to job satisfaction, (2) the supervision of leadership, work motivation, and job satisfaction simultaneously and significantly affect the business progress , and (3) the supervision of leadership and motivation of work simultaneously and significantly affect business progress through job satisfaction. Keywords : Supervision of Leadership, Work Motivation, Job Satisfaction, and Business Progress